Simultaneous quantification of Cd(II) and Pb(II) in surface marine sediments using Ag–Hg and Ag–Bi nanoalloys glassy carbon modified electrodes. Issue 5 (May 2021) - Valera, Danny; Fernández, Lenys; González, Gema; Romero, Hugo; Martínez, Omar; Espinoza-Montero, Patricio J.
Abstract: The evaluation of glassy carbon (GC) electrodes modified with a Nafion (Nf) film and doped with nanoalloys (Nys) deposits of Ag–Hg and Ag–Bi and their application to determination of Cd (II) and Pb(II) in marine sediments, is described. Deposited Ag–Hg and AgBi Nys have a size of approximately ~80 nm dispersed and embedded inside the booths of the Nf net, while other of them remained on Nf net surface. For the AgBiNysNf-GC electrode, a detection limit (DL), 3 s criterion, slightly higher than for the AgHgNysNf-GC modified electrode was obtained. Accuracy of measurements was asserted by comparison with quantification of Cd and Pb in three sets of marine sediments samples previously analyzed by inductively coupled plasma optical emission spectroscopy (ICP-OES). The values of the standard deviation and the coefficients of variation are very low, and also comparable between the different determinations. Abstract : Bimetallic nanoparticles, ICP-OES spectroscopy, Modified Electrodes, Pb and Cd Anodic Stripping Voltammetry